Comprehensive evaluation of primary health care service capacity in China based on TOPSIS and RSR methods - Wang, Lingyi; Li, Furong; Jiang, Shan; Xia, Jingjie (Frontiers in Public Health, 2025)
BackgroundPrimary health institutions form the foundation of China’s three-tiered medical and health service system in both urban and rural settings, shouldering the critical role of delivering basic medical and healthcare services to the populace. Gaining insight into the capacity of primary health care services in China post the 2009 New Health Reform is of paramount importance for further safeguarding public health and advancing health equity.MethodsUsing national data from the China Health Statistics Yearbook from 2009 to 2022, we constructed an evaluation system with 14 indicators across three dimensions: health resource input, health service efficiency, and health service output. We employed an entropy-weighted Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS), Rank-Sum Ratio (RSR) method and fuzzy combination evaluation to objectively assess PHC capacity and its constituent parts. Sensitivity analysis was performed to test the robustness of the comprehensive ranking results. The data analysis was meticulously executed using the R4.4.2 software.ResultsThe overall comprehensive evaluation score showed a general upward trend, peaking in 2022. However, dimensional analysis revealed a stark divergence: the “Health Resource Input” dimension improved steadily over the period, while the “Health Service Efficiency” dimension showed a clear declining trend, with the most efficient years being at the beginning of the study period.ConclusionChina’s PHC capacity growth from 2009 to 2022 has been primarily driven by a massive expansion in resources, which masks a persistent and worrying decline in service efficiency. Our objective, multi-dimensional analysis reveals a critical need for a policy pivot from simple resource accumulation to strategic performance optimization. Future efforts must focus on improving the operational efficiency of existing assets and enhancing the quality of care to ensure sustainable and high-value primary health care for the population.